(3Mb GdEOGQI ai JYOjd YbhO GdHhJ (BB. O. T / s - (3YHOGdefYe GdYeGQi Ydi CHh HQjb s; (3LGHQ LGO fUGQ s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2010)
(3XgQJ YbhO GdHhJ cEMOi hSGFd Jehjd GdeTQhYGJ GdYGeI GdJi Jchf GdOhdI Ch EMOi GdLgGJ GdEOGQjI GdJGHYI dgG CMO CWQGa gPG GdYbO hgi GdJi JefM gPG GdGeJjGR dTQcI GdeTQhY hHGdJGdi jchf dgG (B- (3Ci GdLgI GdEOGQjI (B- (3SdWGJ hGSYI Ydi YbhO GdHhJ eeG jLYdgG ai eQcR eJejR Yf GdeJYGbO eQO Pdc JZdjH GdeUdMI GdYGeI Yf GdeUdMI GdNGUI hef Hjf gPg GdSdWGJ GdeefhMI ddGOGQI SdWJgG ai JYOjd YbhO GdHhJ ai MGd JZjQ GdXQha ShGA hLO fU ai GdYbO Ydi SdWI GdJYOjd Ce de jhLO hai ebGHd SdWI GdEOGQI ai JYOjd GdYbO HEQGOJgG GdefaQOI aEf gfGc MbG ddeJYGbO ai ehGLgI SdWI GdJYOjd gPgs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdYGe, (B2010s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B215-227s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdYGes; (3JYOjd YbhO (BB. O. Ts; (3Mb GdEOGQI s; (3YbhO GdHhJs; (3SdWI GdJYOjds; (3GdJhGRf GdeGdjs; (3GdeJYGbOs; (3GdJYhjVs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdYGes